Regionalism in a Multilateral World - Ethier, Wilfred J. (Journal of Political Economy, 1998)
Recent regional initiatives have been addressed from a Vinerian perspective of trade creation and trade diversion. This is true of both policy‐oriented economists, who tend to be critical of the initiatives, and theorists, who have added dynamic and gametheoretic elements to the Vinerian structure. This paper describes the stylized facts of much recent regional integration and develops an alternative model. The analysis suggests that regional integration, far from threatening multilateral liberalism, may in fact be a direct consequence of the success of past multilateralism and an added guarantee for its survival.